A qualitative study of teacher talk in an EFL classroom interaction in Aceh Tengah, Indonesia - Nasir, Chairina; Yusuf, Yunisrina Qismullah; Wardana, Andri (Indonesian Journal of Applied Linguistics, 2019)
Teacher talk plays an essential role in classroom interaction since it can facilitate students to enhance their levels of comprehension toward the learning materials and further encourage them to be more active during the learning process. This qualitative study is aimed to analyze the types of talk employed by the teacher in the classroom interaction based on the framework of Flanders Interaction Analysis Category System (FIACS) promoted by Flanders (1970). The data were collected through audio recording and observation for three class meetings, and interview with the teacher at the second grade of a senior high school in Aceh Tengah, Indonesia. The results showed that all of the seven types of teacher talk were found. Among them, giving directions took place as the most applied interaction by the teacher. It indicates that the teacher mostly controlled and provided the students with directions, commands, or orders in the learning process. Meanwhile, the least used were accepting or using ideas of pupils and accepting feelings. From the result of the interview, this matter occurred due to the lack of students’ participation in expressing their ideas and feelings. Thus, this study is expected to be a reference by which teachers could consider the types of teacher talk to be implemented to improve their students’ activity and interest during the classroom interaction.